Characteristics and Distribution of Great Argus (Argusianus argus) Display Courts in the Soraya Research Station, Aceh, Indonesia - S, Feri Sandria; Fithri, Aida; Rasnovi, Saida (Elkawnie, 2026)
Abstract: The Great Argus (Argusianus argus) is a ground-dwelling pheasant species whose reproductive behavior is characterized by the establishment and maintenance of display courts used during courtship. Information on the distribution and habitat characteristics of these display courts remains limited, particularly in Sumatra. This study aimed to assess the distribution and characterize the habitat conditions associated with Great Argus display courts at the Soraya Research Station (SRS), Aceh, Indonesia. Field surveys were conducted from April to July 2024 to locate display courts and evaluate their surrounding habitat characteristics. Vegetation data were collected using 40 sampling plots (20 × 20 m) established around the identified display courts.A total of 10 display courts were recorded within an approximately 500-ha study area. Display courts were located at elevations ranging from 120 to 207 m above sea level and on slopes of 2–19°, indicating a preference for relatively flat to gently sloping terrain. The mean display court perimeter and area were 26.8 m and 58.07 m², respectively. Environmental conditions surrounding the display courts were characterized by a mean air temperature of 27.0°C, soil temperature of 27.3°C, light intensity of 378.4 cd, relative humidity of 76.5%, and soil pH of 6.6. Vegetation analysis revealed a high level of tree species diversity, with a Shannon–Wiener diversity index (H′) of 4.43. The highest Importance Value Index (IVI) values were recorded for Streblus elongatus and Artocarpus sp., indicating their dominance within the vegetation community surrounding several display courts. The occurrence of display courts in areas with high tree diversity and specific topographic conditions suggests that habitat structure may influence display court establishment by Great Argus. These findings provide important ecological information for understanding habitat requirements of the species and may contribute to the development of conservation and habitat management strategies for Great Argus populations in Aceh and other parts of Sumatra. Abstrak: Kuau raja (Argusianus argus) merupakan salah satu spesies burung dari famili Phasianidae yang memiliki perilaku unik berupa pembuatan arena kawin (display court) sebagai tempat untuk menarik pasangan selama musim reproduksi. Penelitian ini bertujuan untuk mengkaji sebaran dan karakteristik arena kawin kuau raja di Stasiun Penelitian Soraya (SPS), Aceh. Penelitian dilaksanakan pada April hingga Juli 2024. Metode yang digunakan meliputi metode jelajah untuk mengidentifikasi dan memetakan sebaran arena kawin serta metode purposive sampling untuk menganalisis vegetasi di sekitar arena kawin. Sebanyak 40 plot pengamatan berukuran 20 × 20 m ditempatkan di sekitar arena kawin yang ditemukan. Hasil penelitian menunjukkan bahwa terdapat 10 arena kawin yang tersebar pada area seluas sekitar 500 ha dengan kisaran ketinggian 120–207 m di atas permukaan laut dan kemiringan lereng 2–19°. Kuau raja cenderung membangun arena kawin pada lokasi dengan topografi datar hingga landai. Rata-rata keliling arena kawin mencapai 26,8 m dengan luas rata-rata 58,07 m². Kondisi lingkungan di sekitar arena kawin ditandai oleh suhu udara rata-rata 27,0°C, suhu tanah 27,3°C, intensitas cahaya 378,4 cd, kelembapan relatif 76,5%, dan pH tanah 6,6. Analisis vegetasi menunjukkan bahwa keanekaragaman jenis pohon di sekitar arena kawin tergolong tinggi, dengan nilai indeks keanekaragaman Shannon–Wiener (H') sebesar 4,43. Jenis pohon yang memiliki Indeks Nilai Penting (INP) tertinggi pada beberapa arena kawin adalah Damli (Streblus elongatus) dan Cempedak Air (Artocarpus sp.). Hasil penelitian menunjukkan bahwa keberadaan arena kawin kuau raja berkaitan erat dengan kondisi habitat, terutama struktur vegetasi dan karakteristik topografi. Temuan ini dapat menjadi dasar ilmiah dalam upaya konservasi dan pengelolaan habitat kuau raja, khususnya di Stasiun Penelitian Soraya, Aceh.